1988
DOI: 10.1177/0265407588054006
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Risk in Intimacy

Abstract: Two studies were conducted to design and validate a measure of perceptions of risk in intimacy. A 10-item scale with high internal consistency was developed and related to romantic involvement, self-esteem, assertiveness, interpersonal trust, sensation seeking, extraversion and attitudes toward love. Individuals who scored high on this `Risk in Intimacy Inventory' (i.e. who perceived high levels of risk in intimate relationships) reported fewer close relationships, less assertiveness, diminished trust in other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
53
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(59 citation statements)
references
References 7 publications
3
53
0
Order By: Relevance
“…On the surface, such an interpersonal style might appear unlikely to relate to social difficulties; however, it could signify a reluctance to take the interpersonal risks necessary for all but the most superficial relationships. Such a self-protective pattern of behavior has been associated in prior studies with limited self-disclosure and a tendency to distance oneself from others, which in turn have been shown to elicit negative reactions from peers (Meleshko & Alden, 1993;Pilkington & Richardson, 1988).…”
Section: Resultsmentioning
confidence: 85%
“…On the surface, such an interpersonal style might appear unlikely to relate to social difficulties; however, it could signify a reluctance to take the interpersonal risks necessary for all but the most superficial relationships. Such a self-protective pattern of behavior has been associated in prior studies with limited self-disclosure and a tendency to distance oneself from others, which in turn have been shown to elicit negative reactions from peers (Meleshko & Alden, 1993;Pilkington & Richardson, 1988).…”
Section: Resultsmentioning
confidence: 85%
“…Nezlek & Pilkington, 1994;Pilkington & Richardson, 1988), they may have actually experienced more of the risks associated with intimacy. Moreover, because of their lower selfesteem (Pilkington & Richardson, 1988) and their lack of confidence (Nezlek & Pilkington, 1994), high-RII individuals may experience stronger reactions to relational problems; that is, they may be in greater danger because of a lack of coping skills. Both possibilities would inflate their danger ratings relative to those of low-RII individuals, who may have personally experienced fewer or less extreme risks and/or coped with them better.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, we believe that other sources of motivation, such as one's feelings of commitment toward a relational partner, may act to lower one's assessment of risks with respect to a partner (cf. Pilkington & Richardson, 1988).…”
Section: Perceptions Of a Partner As A Source Of Harm To The Selfmentioning
confidence: 99%
“…The commitment-trust linkage is also relevant. Past research has demonstrated that as trust increases, an individual's belief in the potential for harm from one's Commitment and Perceptions of Harm 11 partner tends to decrease (e.g., Appleby et al, 1999;Kline, Kline & Oken, 1992;Misovich, Fisher & Fisher, 1997;Pilkington & Richardson, 1988). …”
Section: Commitment Transformation Of Motivation and Harm Perceptionsmentioning
confidence: 99%